NEW STRATEGIES IN LIVER SURGERY FOR IV STAGE METASTATIC COLORECTAL CANCER. - Nikola Y. Kolev; Anton Y. Tonev; Valentin L. Ignatov; Georgi H. Ivanov; Aleksander K. Zlatarov; Georgi Todorov; Velian Platikanov; Krasimir D. Ivanov (Peytchinski Publishing, 2012)
With recent advances in chemotherapy, traditional clinicopathological factors should not be used to exclude otherwise resectable patients from surgery. Pathological or clinical response to chemotherapy has become valuable in determining the treatment for individual patients. Portal vein embolization and two-stage operation with ablative therapy and preoperative chemotherapy should be considered for unresectable liver metastases located in a liver remnant that is at the minimum volume required for survival. The recent E0RTC 40983 trials regarding preoperative chemotherapy for resectable CLM have failed to demonstrate a clear significant advantage. However, patients with a low clinical risk score for the recurrence, such as several metastases of less than 4 cm, and who are fit candidates for liver resection are often offered immediate surgery. Patients at high clinical risk should also be considered for neoadjuvant chemotherapy. One forthcoming and appealing strategy is to adapt postoperative treatment according to tumor response as evaluated by neoadjuvant chemotherapy or by the presence of individual tumor biomarker such as the Kras mutation or single-nucleotide polymorphisms. This could avoid the overtreatment of nonresponsive patients and enable a more tailored approach to treat an individual patient's disease. The treatment paradigm for CLM is rapidly changing with the development of newer anticancer chemotherapeutic agents.